Sistem Pendukung Keputusan Aplikasi Nobar Online Terbaik Dengan Menerapkan Metode EDAS Dengan Pembobotan ROC - Serta Kurniawan Zega; Amran Saleh Harahap; Helfrida Hormaria Sihite; Imam Saputra (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
The online Nobar application is an application that provides various kinds of films or videos that are made to provide practicality for users to do online Nobar. The online Nobar application has been widely circulated on Google Playstore so that it allows users to do online Nobar wherever and whenever, so in this case a Decision Support System (SPK) is needed in determining the online Nobar application which must be recommended by the general public. In determining it there are several alternatives and criteria including user reviews, genres, users, ratings, paid videos. A decision support system is needed in determining the appropriate online nobar application to be recommended istance from average solution) method producing the best preferences according to data such as alternatives and criteria which has been determined and the best preference value in the 3rd Alternative, namely Viu as the best application for Nobar Online with a value of 0.3265with a combination of the ROC (Rank order Centroid) method and generating weight values for certain criteria and the EDAS (d.